THU0008 GM-CSF PATHWAY SIGNATURE IDENTIFIED IN TEMPORAL ARTERY BIOPSIES OF PATIENTS WITH GIANT CELL ARTERITIS. (June 2019) - Cid, Maria C.; Gandhi, Rohan; Corbera-Bellalta, Marc; Muralidharan, Sujatha; Paolini, John F.
Abstract : Background: Giant Cell Arteritis (GCA) is a type of large vessel vasculitis that can cause blindness and aortic aneurysms. A significant unmet medical need remains in GCA, as current treatment options are limited, and relapse increases corticosteroid (CS) exposure and toxicity. The primary role of macrophages/dendritic cells (DCs) and TH 1/TH 17 lymphocytes in GCA pathogenesis has been highlighted previously. Granulocyte-macrophage colony stimulating factor (GM-CSF) may contribute to GCA pathogenesis by stimulating giant cell formation. 1 GM-CSF produced by CD4 + T helper TH 1 and TH 17 cells can stimulate conventional DCs and promote differentiation of monocyte-derived DCs. 2 GM-CSF may drive DCs to program naïve CD4 + cells to TH 1, TH 17, and T follicular helper phenotypes (IFNγ/IL-17/IL-21). Notably GM-CSF RNA has been reported in GCA lesions 3 and in peripheral blood mononuclear cells of symptomatic patients. 4 Objectives: We hypothesized elevation of the GM-CSF pathway signature in GCA vessels versus controls. Methods: Two independent sources of temporal artery biopsies were utilized. First, GCA (n=17) and control (symptomatic patients suspected for GCA, but with a normal temporary artery biopsy; n=5) biopsies were analyzed for 15 mRNA transcripts representing TH 1, TH 17, and GM-CSF signaling (RNAscope; RS) and for mRNA transcripts representing the autoimmune panel (Nanostring; NS). Semi-quantitative scoring was performed on RS images, and fold-change of representative TH 1, TH 17 and GM-CSF related mRNA transcripts were calculated via NS nCounter analysis. Additional GCA and control biopsies were obtained and analyzed by RT-PCR for a subset of transcripts (n=10 each) and by confocal microscopy for GM-CSF and GM-CSF-Rα protein (n=2 each). Results: The GM-CSF signaling pathway molecular signature was confirmed to be upregulated by 4 independent analyses. GM-CSF-associated and TH 1-associated genes were upregulated in GCA biopsies versus control (GMCSF: 3-4x RS; GM-CSF-Rα: 6.7x NS, 6x RS; and CD83: 3.9x NS, 6x RS; TNFα: 2x NS, 3x RS; IFNγ: 2x RS; IL-1β: 6x RS). TH 17 associated genes were not elevated, potentially due to concomitant CS treatment. Upregulation of both GM-CSF (12x) and GM-CSF-Rα (3x) mRNA was confirmed in a separate cohort of biopsies from GCA patients vs. controls by RT-PCR (Figure). GM-CSF and GM-CSFRα proteins were detected in the luminal endothelium, neovessels and inflammatory cells of GCA patients. In normal temporal arteries, GM-CSF protein was not detected, and some GM-CSFRα expression was observed in the luminal endothelium. Pu.1, a transcription factor downstream of GM-CSF signaling, was increased 8x in GCA vs. controls (RS, NS) (Figure). Conclusion: GM-CSF and TH 1 pathway signatures were demonstrated in GCA patient temporal arteries by independent analytical techniques. Active GM-CSF signaling in diseased tissue is evidenced by increased expression of Pu.1 in the vessel wall. These data implicate the GM-CSF pathway in GCA pathophysiology and increase confidence in rationale for targeting GM-CSF in GCA. References: [1] M-CSF and GM-CSF promote alveolar macrophage differentiation into multinucleated giant cells with distinct phenotypes. Lemaire et al, 1996. Journal of leukocyte biology, 60(4):509-18. [2] Targeting GM-CSF in inflammatory diseases. Wicks & Roberts, 2016. Nature reviews. Rheumatology, 12(1):37-48. [3] Tissue cytokine patterns in patients with polymyalgia rheumatica and giant cell arteritis. Weyand et al, 1994. Annals of internal medicine, 121(7):484-91. [4] Interleukin-21 modulates TH1 and TH17 responses in giant cell arteritis. Terrier et al, 2012. Arthritis and rheumatism, 64(6):2001-11. Disclosure of Interests: Maria C. Cid Grant/research support from: Kiniksa Pharmaceuticals, Consultant for: Roche, GSK, Janssen, Abbvie, Speakers bureau: Boehringer-Inhelheim, Vifor, Rohan Gandhi Shareholder of: Kiniksa Pharmaceuticals (clinical development stage biopharmaceuticals company), Employee of: Currently employed at Kiniksa Pharmaceuticals, Marc Corbera-Bellalta: None declared, Sujatha Muralidharan Shareholder of: Kiniksa Pharmaceuticals (clinical development stage biopharmaceutical company), Employee of: Currently employed at Kiniksa Pharmaceuticals, John F. Paolini Shareholder of: Kiniksa Pharmaceuticals (clinical development stage biopharmaceutical company), Employee of: Currently employed at Kiniksa Pharmaceuticals